Comprehensive characterization of horse genome variation by whole‐genome sequencing of 88 horses. (7th December 2018) - Jagannathan, V.; Gerber, V.; Rieder, S.; Tetens, J.; Thaller, G.; Drögemüller, C.; Leeb, T.
Summary: Whole‐genome sequencing studies are vital to gain a thorough understanding of genomic variation. Here, we summarize the results of a whole‐genome sequencing study comprising 88 horses and ponies from diverse breeds at 19.1× average coverage. The paired‐end reads were mapped to the current EquCab3.0 horse reference genome assembly, and we identified approximately 23.5 million single nucleotide variants and 2.3 million short indel variants. Our dataset included at least 7 million variants that were not previously reported. On average, each individual horse genome carried ∼5.7 million single nucleotides and 0.8 million small indel variants with respect to the reference genome assembly. The variants were functionally annotated. We provide two examples for potentially deleterious recessive alleles that were identified in a heterozygous state in individual genome sequences. Appropriate management of such deleterious recessive alleles in horse breeding programs should help to improve fertility and reduce the prevalence of heritable diseases. This comprehensive dataset has been made publicly available, will represent a valuable resource for future horse genetic studies and supports the goal of accelerating the rates of genetic gain in domestic horse.